Application of Hybrid Contract Concept in Giro Product - Septiana Putri, Cindy; Herdiana Abdurrahman, Nana; Prasetyo, Yoyok (Yayasan Mentari Madani, 2024)
An agreement is a form of agreement between parties to do something. An agreement always gives birth to an agreement, where the agreement is a concrete form and the agreement is an abstract and binding form. The concept of contract product innovation has emerged by combining several existing contracts and is called a hybrid contract. A hybrid contract is a combination of two or more contracts into one contract for a specific purpose. This research was conducted to determine the application of hybrid contracts in sharia financial institution products, especially Giro. This research also analyzes whether the application of Giro products in sharia banking is in accordance with Islamic law. The type of research used is library research by describing qualitative data obtained from research documents. This research uses qualitative methods combined with analytical methods. The research results show that the implementation of hybrid contracts in Giro products in sharia banking is in accordance with the provisions of Islamic law. Combination contract products are permitted in accordance with religious texts so that Giro products can be claimed to be included in the contract category which applies to several contracts, especially wadiah and mudharabah contracts. In the Sharia Bank Giro product, there is a basic contract, namely a deposit and includes additional fees. contracts, especially benefits. From this agreement there will be an agreement to determine profits with the mudharabah giro.